IIT JEE 1983 Maths - MCQ Question 14

Geometry Level 3

If f ( x ) = cos ( ln x ) f(x)=\cos (\ln x) , then f ( x ) f ( y ) 1 2 [ f ( x y ) + f ( x y ) ] f(x)f(y)-\frac12\left[f\left(\frac{x}{y}\right)+f(xy)\right] simplifies to which of the following numbers?


In case you are preparing for IIT JEE, you may want to try IIT JEE 1983 Mathematics Archives .
2 -2 1 2 \frac12 1 -1 None of the others

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

f ( x ) f ( y ) = cos ( ln x ) cos ( ln y ) As cos A cos B = 1 2 [ cos ( A B ) + cos ( A + B ) ] = 1 2 [ cos ( ln x ln y ) + cos ( ln x + ln y ) ] = 1 2 [ cos ( ln ( x y ) ) + cos ( ln ( x y ) ) ] = 1 2 [ f ( x y ) + f ( x y ) ] \begin{aligned} f(x)f(y) & = \cos(\ln x) \cos (\ln y) & \small \color{#3D99F6} \text{As } \cos A \cos B = \frac 12[\cos(A-B)+\cos(A+B)] \\ & = \frac 12[\cos(\ln x-\ln y)+\cos(\ln x + \ln y)] \\ & = \frac 12 \left[\cos \left(\ln \left(\frac xy \right) \right)+\cos (\ln (xy))\right] \\ & = \frac 12 \left[f \left( \frac xy \right)+ f(xy) \right] \end{aligned}

f ( x ) f ( y ) 1 2 [ f ( x y ) + f ( x y ) ] = 0 \begin{aligned} \implies f(x)f(y) - \frac 12 \left[f \left( \frac xy \right)+ f(xy) \right] & = 0 \end{aligned}

Therefore, the answer is None of the others \boxed{\text{None of the others}} .

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...